MEMOTRET POLA FRAUD PADA RINCIAN OBJEK BELANJA YANG MENJADI TEMUAN BPK - Siti sholihah; M. Nizarul Alim; Siti Musyarofah (JAFFA, 2016)
The purpose of this study to analyze the patterns of fraud on the 19 object details shopping becomes BPK in SKPD Mahkota. The reseach design is case study in SKPD Mahkota which SKPD with the biggest finding in Pemkab Singgasana. The informant is the financial manager at SKPD Mahkota. The results showed that fraud on the details of the object shopping becomes BPK in SKPD Mahkota occur starting from the planning stage, the stage of implementation and administration as well as the stage of reporting and accountability. Fraud in the third stage was conducted jointly by the planners, PPTK, treasurer and PPK.